Donepezil–ferulic acid hybrids as anti-Alzheimer drugs. (January 2015) - Benchekroun, Mohamed; Ismaili, Lhassane; Pudlo, Marc; Luzet, Vincent; Gharbi, Tijani; Refouvelet, Bernard; Marco-Contelles, José
Background: Due to the complex nature of Alzheimer's disease, there is a renewed and growing search for multitarget drugs.Results: Donepezil–ferulic acid hybrids (DFAHs) were prepared by the one-pot Ugi-4CR in low-to-moderate yields. DFAHs are potent antioxidant agents, showing oxygen radical absorbance capacity values in the range 4.80–8.71 trolox equivalents, quite higher compared with those recorded for ferulic acid and melatonin. From the ChEs inhibition studies, we conclude that DFAH 8, bearing an ethylene linker, and DFAH 12, bearing a propylene linker, both substituted with a melatonin motif, are the most potent inhibitors, in the nanomolar range.Conclusion: We have identified DFAH 8 as a very potent antioxidant, and totally selective equineButyrylCholinEsterase (eqBuChE) inhibitor.